Childbirth Experiences of Socially Vulnerable Women and Their Associations with the Risk of Postpartum Depression and Post-Traumatic Stress Disorder - Gabrijolavičienė, Lina; Šumskienė, Egle (Socialinė teorija, empirija, politika ir praktika, 2026)
Background: Socially vulnerable women are at an increased risk of negative childbirth experiences and subsequent postpartum mental health difficulties; however, empirical evidence on these associations remains limited in the Lithuanian context. Aim: This study aimed to examine childbirth experiences among socially vulnerable women and their associations with the risk of postpartum depression and post-traumatic stress disorder (PTSD) symptoms in comparison with women not experiencing social vulnerability. Methods: The study analysed data from the nationwide survey carried out in 2023 “My Childbirth” (N = 1,471), conducted among women who gave birth in Lithuanian hospitals. Results: Socially vulnerable women were significantly more likely to report negative childbirth experiences (21% vs. 13%) compared to non-vulnerable women. They also demonstrated a higher risk of postpartum depression (30% vs. 22%) and PTSD symptoms (10% vs. 5%). Negative childbirth experiences were strongly associated with an increased risk of both postpartum depression and PTSD symptoms. Conclusions: Subjective childbirth experiences play a central role in postpartum emotional wellbeing; whereas, social vulnerability constitutes a significant risk condition for both negative childbirth experiences and adverse mental health outcomes.
Keywords: traumatic birth experience; postpartum depression; post-traumatic stress disorder; social vulnerability